The Present Value of Corporate Profits : A Forecasters' Survey Perspective - Andrle, Michal (IMF Working Papers; Working Paper ;, 2019)
This paper presents and discusses the estimates of the present value of corporate profits in the United States from 1984 to 2018. To value the expected income stream, it uses the long-range forecasts of professional forecasters for pre-tax corporate earnings and long-term Treasury note yields, sourced from the Blue Chip Economic Indicators survey. The appraised value of corporate earnings can point in real time at periods where market prices are deviating from valuations implied by expected earnings and interest rates. Market participants' forecasts seem to interpret most of the earnings fluctuations as permanent, underestimating the cyclical fluctuations The over-reaction to transitory shocks and changes in long-term outlook leads to swings in the valuation, in line with swings in the observed market prices.